Effect of processing of dental drill noise on subjective impression. (June 2021) - Yamada, Tomomi; Kuwano, Sonoko; Ebisu, Shigeyuki; Hayashi, Mikako
Highlights: Subjective impressions of 40 stimuli based on dental drill sounds were measured. Overall attenuation of the sound level by 5 dB and 10 dB statistically improved. Attenuation of a part of the acoustical peaks alone was not sufficient for improving. High-frequency components over 9 kHz influenced unpleasantness. Abstract: The sound produced by a dental air turbine handpiece (dental drill) can markedly influence the sound environment in a dental clinic, and many patients have reported that the sound of a dental drill elicits unpleasant feelings. A comfortable sound environment for patients is desirable in medical care. To identify approaches for improving the sound quality of dental drills, we need to determine systematically the effects of the physical properties of the sounds of dental drills on their impressions. We, therefore, prepared 40 sound stimuli by processing different sound levels or frequency components comprising the sounds emitted by four kinds of dental drills. This study is designed to use psychoacoustic experiments to determine the effects of dental drill sounds on subjective impressions. The analysis resulted in the following findings: the overall attenuation of each original sound stimulus by 5 dB or 10 dB had statistically significant effects and improved the unpleasant impression. Attenuation of the frequency components above 9 kHz by 10 dB also improved the impressions, relative to those for the original sound stimuli. When the prominent frequency components at approximately 6 kHz were attenuated by 10 dB, no statistically significant differences were observed between the impressions corresponding to the original and processed stimuli. The Comfort Index ( CI ), which consists of the equivalent continuous A-weighted sound pressure level ( L Aeq ) and calculated sharpness, showed a good correlation with unpleasant impressions. The present findings suggest that the consideration of acoustical characteristics based on the CI is useful in reducing the sound pressure level and refining the frequency characteristics of sounds emitted by dental drills, and this can aid in the development of new dental devices to create a comfortable sound environment in dental clinics.